Cotton (Gossypium hirsutum) establishment methods based systemintensification: Effects on Bt cotton growth, weed suppression, system crop and water productivity, system-profitability and landâ€“use efficiency in Indoâ€“ Gangetic plains region - RAJPOOT, SUDHIR K; RANA, D S; CHOUDHARY, ANIL K; PANDE, POOJA (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted at IARI, New Delhi during 2014-15 and 2015-16 to study the effect of Bt cotton (Gossypium hirsutum L.) establishment methods (CEMs) and planting geometry on plant growth, yield and weed suppression behaviour in Bt cotton vis-Ã -vis system productivity, profitability, water-productivity, production-efficiency, economic-efficiency and land use efficiency. The experiment was laid out in split-plot-design with four replications comprising two CEMs [transplanted-cotton (TPC) and direct-seeded-cotton (DSC)] and three planting geometries/plant densities [(90Ã—60 cm (18,518 plants/ha); 75 Ã— 45 cm (29629 plants/ha) and 60Ã—45 cm (37,037 plants/ha)] and four cropping systems viz. TPCâˆ’wheatâˆ’mungbean; TPCâˆ’onionâˆ’fodder cowpea + maize; DSCâˆ’wheat; and DSCâˆ’onion cropping system under above two CEMs. Among CEMs, the DSC-cotton resulted in higher plant growth though the seed yield and lint yield were respectively higher by 9.54% and 15% under TPC-cotton over DSC-cotton due to better plant stand in TPCâ€“CEM. On an average, the significantly highest system productivity in terms of seed-cottonequivalent- yield (SCEY) was registered in TPCâˆ’wheatâˆ’mungbean/TPCâˆ’onionâˆ’fodder cowpea + maize cropping systems (mean of both systems) during 2014â€“15 (6.75 t/ha) and 2015â€“16 (6.96 t/ha), respectively. In general, the legume-intensification in TPCâ€“based cropping systems exhibited about 25 to 27% higher system yield (SCEY) over DSCâ€“based cropping systems. The TPCâ€“based cropping systems exhibited additional net economic gains of ` 43000/ ha vis-Ã -vis higher weed suppression, system crop and water productivity, system economic-efficiency and landâ€“use efficiency over the DSCâ€“based systems. Likewise, planting geometry/planting density of 60 Ã— 45 cm (37037 plants/ ha) exhibited significantly higher system productivity (SCEY) (6.58 t/ha), system net returns (` 178450/ha), system water-productivity and system economic-efficiency over other two planting geometries viz. 75 Ã— 45 cm and 90 Ã— 60 cm. In nutshell, system-intensification through transplanted Bt-cotton based cropping systems (TPCâˆ’wheatâˆ’mungbean/ TPCâˆ’onionâˆ’fodder cowpea + maize) and planting geometry/planting density of 60 Ã— 45 cm (37037 plants/ha) led to higher weed suppression, system productivity, system economic-efficiency, system water-productivity and landâ€“use efficiency in Indoâ€“Gangetic plains region.